Using the Financial Analysis of Financial Information Published in the financial Statements for Predicting Stocks returns of Services and Insurance Sectors (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of this study was to identify the rate of return of the stock through the financial information disclosed by the financial statements of companies both services and insurance included in Iraqi market for securities . The study used a descriptive statistical methods and the correlation matrix for the independent factors , in addition to a regression model for data  analysis and hypothesis . Model included a number of independent variables , which was measured in the size of company (sales or revenue) , and the leverage , in addition to the structure of assets and the book value of owners'  equity in the company , as well as the general price index .Based on the data of (11)companies and for three years, showed the results of this study , that the majority of these financial variables do not affect statistically significant returns on the shares of those companies , except for the size of the company  for the years (2011) , (2012) and the general price index for the years (2012) their impact was significant and positive return on stocks.The study showed a strong positive relationship  between the independent variables and the dependent variable for the Years                            (2010),(2011),(2012)Respectively.